KERANGKA KERJA PENGUKURAN SOCIAL MEDIA RETURN ON INVESTMENT - Endang Hariningsih (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2016)
The use of social media is increasingly being used to the level of the individual, the community and the business world. The purpose of paper is to summarize the diverse framework for measuring social media return on investment. Measurement of social media return on investment is not enough just to measure in terms of financial return. Because not all forms of marketing investment can be quantified in the form of finance.Social Media ROI measurement based on the calculation of financial and non-financial. Financial calculations are based on a formula gains from SM divided the investments made for the use of SM. To combine financial and non-financial measurements, several studies have diverse point of views. Viewpoint among others who base measurement SM ROI taking into account; such as: differences in the unit of analysis, based on benefit of SM, using Method Based Process BCCP (Brand building, Community building, Customer Satisfaction and Loyalty, and economic Performance. It can also be used framework for measuring SM ROI on the basis of Brand Awareness, Brand Engagement, and Word of Mouth.Keywords: social media, return on investment, financial, non-financial